Foreign Direct Investment in Hazardous Industries in Developing Countries: Rethinking the Debate - Jennifer Clapp (Environmental Politics, 1998)
It is often asserted that the debate over industry location and the environment is closed. It is argued MNCs do not invest in highly polluting industries in developing countries in order to take advantage of weaker environmental regulations, as environmental costs are not sufficient to warrant industry relocation. This article argues that this assertion may not always hold for foreign direct investment in the most highly hazardous industries in developing countries, and that there is reason to revisit this debate. In addition, there has been a growing incidence of FDI and double standards practised by MNCs in hazardous industries in the South in the past decade, while at the same time very little has been done to transfer clean production technologies. Recent voluntary environmental initiatives on the part of global industry do not seem to have changed the situation. Instead, there seems to be growing concentration of so‐called ‘green’ investment in clean‐up, rather than clean technologies. Though such technologies may help to remediate contaminated sites and provide a place to put hazardous wastes produced in developing countries, they do not do much to help to avoid the generation of hazardous wastes in the first place.